2010
DOI: 10.1007/s11002-010-9129-7
|View full text |Cite
|
Sign up to set email alerts
|

Ambivalence toward a country and consumers’ willingness to buy emblematic brands: The differential predictive validity of objective and subjective ambivalence measures on behavior

Abstract: Previous country-of-origin research has treated opinions of countries as either positive or negative, even though people may in fact hold conflicting opinions about countries. The extant literature on ambivalence suggests that the coexistence of positive and negative opinions of a country should increase avoidance of objects associated with that country, above and beyond the effects of mere positivity or negativity. Data collected from French consumers who varied in degrees of ambivalence toward the US reveal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 53 publications
2
16
0
Order By: Relevance
“…In this study, this notion is applied to luxury brands made in France and sold in the United States. One country‐of‐origin study, which tested French consumers’ perception of American brands, can be found in the literature, but it was not done in the context of luxury brands (Russell, Russell, & Klein, ). Another study on attitude toward luxury, based on 20 countries, can be found in the literature (Dubois, Czellar, & Laurent, ).…”
Section: Context Of the Study Vs Luxury Brandsmentioning
confidence: 99%
“…In this study, this notion is applied to luxury brands made in France and sold in the United States. One country‐of‐origin study, which tested French consumers’ perception of American brands, can be found in the literature, but it was not done in the context of luxury brands (Russell, Russell, & Klein, ). Another study on attitude toward luxury, based on 20 countries, can be found in the literature (Dubois, Czellar, & Laurent, ).…”
Section: Context Of the Study Vs Luxury Brandsmentioning
confidence: 99%
“…Zhou and Hui (2003) demonstrated that symbolic benefits (such as modernity, prestige, and associations with foreign lifestyles) constitute one of the primary motivating forces of Chinese consumers' purchases of products of nonlocal origin, including products that may not be commonly regarded as conspicuous. Chinese consumers are convinced that using foreign brand products can enhance their personal image (e.g., Russell et al, 2010).…”
Section: National Identity and Chinese Consumersmentioning
confidence: 99%
“…Russell et al found that when people hold a positive and negative view of a country at the same time, the ambivalence will have a negative impact on consumer's willingness to buy the country's brand (Russell & Klein, 2011).…”
Section: Ambivalent Attitudementioning
confidence: 99%